The effect of training in raising the efficiency of employee performance - An exploratory study on governmental and private organizations in Jeddah- - Al-Zahrani, Salih Saeed (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aimed at shed light on the topic of training and its importance in relation to human resources, to identify the methods of success and failure of training programs, to highlight the role of training in improving the performance of human resources and to know the principles on which training is based. The study assumed that there is no significant relationship between training and productivity of workers at a level of statistical significance (α<0.05) , and that there is no significant relationship between training and quality of work at the level of statistical significance (α<0.05) , and that there are no statistically significant differences at the level of significant significance (α<0.05) in employees in the public and private sectors about The effect of training in raising the efficiency of workers. The population of this research consisted of a number of employees in the public and private sectors, and the study sample consisted of a random sample of 50 employees in the public and private sectors. The questionnaire tool was used in the current study, and the statistical method of spss was used using arithmetic averages, standard deviations and variance, The descriptive and analytical approach was used in this study for its suitability to study the phenomenon, and the study concluded that there is no statistically significant relationship at a significance level (0.05) in the responses of the study sample individuals about no significant relationship between training and productivity of workers, and that result confirms the correlation coefficient (Thus the study rejects the first hypothesis that there is no significant relationship between training and productivity of workers, and accepts the alternative hypothesis that there is no significant relationship between training and productivity of workers, and it became clear that there is a statistically significant relationship at a level of significance (0.05) in The responses of the study sample individuals about no statistically significant differences at the level of significant (α<0.05) in the views of employees in the public and private sectors. Especially about the effect of training in raising the efficiency of workers, as the correlation coefficient amounted to (-0.071). The study recommended that employees in the public and private sectors must be given some skills necessary to develop their administrative competencies. Stability must be increased for workers at work, which leads to raising the morale of the trainees. Employees in the public and private sectors are positive towards work and those working with them. Employees in the public and private sectors must be kept abreast of developments in the fields of knowledge related to their work.